Zinc oxide and zeolite imidazolate framework-8 loaded fibers for dual protection against airborne particulate and gaseous pollutants - Kyeongeun Lee; Hanjou Park; Yewon Choi; Juyeon Baek; Jooyoun Kim (Fashion and Textiles)
Abstract The widespread impacts of industrial air pollutants address the urgent need for advanced filtration technologies mitigating various environmental pollutants. This study conducted comparative investigations of zinc oxide (ZnO) and zeolitic imidazolate framework-8 (ZIF-8) treated fibrous composites with subsequent corona charging, to apply as a dual-function air filter that is simultaneously protective against particulate and gaseous matters. While both ZnO and ZIF-8 presented charge-trapping capability, the uniform coating of ZIF-8 nanocrystals on the fibrous material, rather than uneven coating of ZnO aggregates, produced higher charging capacity, leading to a superior electrostatic filtration efficiency. On the other hand, agglomerates of ZnO crystals in the fibrous web advantageously affected the mechanical filtration efficiency, especially in the layered structure. Concerning the SO2 gas adsorption capacity, the inherent pore characteristic of ZIF-8 allowed a superior gas removal performance. The SO2 adsorption was hardly influenced by the post-corona charging process, either for ZnO or ZIF-8 treated composites. This study highlights the advantages of ZIF-8 integration in fibrous composites for the advanced design of dual filters, where ZIF-8 integration not only gives high gas removal performance but also significantly enhances charge trapping ability and the associated electrostatic filtration performance.